New horizons in the study of language and mind - Chomsky, Noam. (Cambridge : Cambridge University Press, 2000)
"In a series of essays, Chomsky cuts through the confusion and prejudice which has infected the study of language and mind, bringing new solutions to traditional philosophical puzzles and fresh perspectives on issues of general interest, ranging from the mind-body problem to the unification of science." "Using a range of simple linguistic analyses, Chomsky argues that there is no coherent notion of "language" external to the human mind, and that the study of language should take as its focus the mental construct which constitutes our knowledge of language. Human language is therefore a psychological, ultimately a "biological object," and should be analyzed using the methodology of the natural sciences. His examples and analyses come together in this book to give a unique perspective on language and the mind."--BOOK JACKET.
Includes bibliographical references and index.
Keywords: Language and languages -- Philosophy; Philosophy of mind